Designing a Problem-Based Learning (PBL) Method for Teaching Moral Values: Trustworthiness and Honesty in Grade VIII at Muhammadiyah 4 Panarukan Junior High School - Arif Syofyan Hadi (World Journal of Islamic Learning and Teaching, 2025)
Moral learning in junior high schools often faces challenges in improving the understanding and application of moral values in everyday life, especially in the material of Trustworthiness and Honesty. This paper is intended to explain the design of the Problem-based learning (PBL) learning method as an innovation in moral learning of the material of Trustworthiness and Honesty in class VIII of SMP Muhammadiyah 4 Panarukan, which is expected to improve students' understanding through a more contextual, active, and applicable learning experience. The PBL method allows students to analyze real problems related to Trustworthiness and Honesty, develop solutions, and reflect on the application of these values in everyday life. This learning design method adopts two stages of the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model, namely the needs analysis stage and the learning design stage. The results of the study indicate that the need for moral learning in class VIII of junior high school includes the importance of more interactive and problem-based methods, which can bridge the gap between moral theory and its application in real life. This PBL learning design integrates case studies, group discussions, and reflection to create meaningful learning experiences related to the values of Trustworthiness and Honesty. Although this design has considered various pedagogical and contextual aspects, the method is still in the design stage and has not been directly implemented or evaluated. Therefore, further research is needed to test the effectiveness of the PBL method in the context of moral learning at SMP Muhammadiyah 4 Panarukan.